2017
DOI: 10.1093/cercor/bhx187
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D Ultrastructure of Thalamocortical Synapses from the “Lemniscal” Ventral Posteromedial Nucleus in Mouse Barrel Cortex

Abstract: Thalamocortical synapses from "lemniscal" neurons of the dorsomedial portion of the rodent ventral posteromedial nucleus (VPMdm) are able to induce with remarkable efficacy, despite their relative low numbers, the firing of primary somatosensory cortex (S1) layer 4 (L4) neurons. To which extent this high efficacy depends on structural synaptic features remains unclear. Using both serial transmission (TEM) and focused ion beam milling scanning electron microscopy (FIB/SEM), we 3D-reconstructed and quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 89 publications
11
61
0
Order By: Relevance
“…Spine head volume in cryo-fixed tissue was 0.069 μ m 3 , which was not different to the spine volume in chemically-fixed tissue of 0.081 μ m 3 (Figure 2). Our spine volume measurements are similar to other studies in the same region of the mouse brain (0.06 ± 0.04 μ m 3 , layer 4 (Rodriguez-Moreno et al, 2017); 0.075 ± 0.005 μ m 3 - 0.079 ± 0.006 μ m 3 , layer 1, adult and aged mice, layer 1(Calì et al, 2018). Similarly, our measurement of mean spine length after cryo-fixation of 0.77 ± 0.55 μ m was not different from the length of 0.84 ± 0.57 μ m in chemically-fixed tissue (Figure 2), and is similar to other studies, for example rat CA1 hippocampus, 0.45 ± 0.29 μ m (Harris and Stevens, 1989); rat cerebellum, 0.66 ± 0.32 μ m (Harris and Stevens, 1988); and mouse layer 2/3 pyramidal cells, 0.66 ± 0.37 μ m (Arellano et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Spine head volume in cryo-fixed tissue was 0.069 μ m 3 , which was not different to the spine volume in chemically-fixed tissue of 0.081 μ m 3 (Figure 2). Our spine volume measurements are similar to other studies in the same region of the mouse brain (0.06 ± 0.04 μ m 3 , layer 4 (Rodriguez-Moreno et al, 2017); 0.075 ± 0.005 μ m 3 - 0.079 ± 0.006 μ m 3 , layer 1, adult and aged mice, layer 1(Calì et al, 2018). Similarly, our measurement of mean spine length after cryo-fixation of 0.77 ± 0.55 μ m was not different from the length of 0.84 ± 0.57 μ m in chemically-fixed tissue (Figure 2), and is similar to other studies, for example rat CA1 hippocampus, 0.45 ± 0.29 μ m (Harris and Stevens, 1989); rat cerebellum, 0.66 ± 0.32 μ m (Harris and Stevens, 1988); and mouse layer 2/3 pyramidal cells, 0.66 ± 0.37 μ m (Arellano et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Remarkably, in both S1-L1 and S1-L5a, a significant number (7%) of the Po axonal varicosities that contained a mitochondrion and synaptic vesicles, lacked any evident synaptic contact. Such “non-synaptic boutons” were also observed in MC-L4/3 Po axons but less frequent (2%), but never in the VPM S1-L4 axons (Table 1; see also 27 ).…”
Section: Resultsmentioning
confidence: 84%
“…Virtually all (95%) VPM synaptic boutons were large, containing one or several mitochondria, large vesicle pools, and most of them (53%) contained more than one (up to four) active zones. Only 5% of the VPM synapses lacked a mitochondrion (interbouton synapses), and no VPM axonal segment containing a mitochondrion inside lacked an active zone 25, 27 (Table 1; Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Most strikingly, synaptic boutons beside layer and area-specific differences (see also Rollenhagen 2015Bopp et al 2017;Hsu et al 2017), differ substantially not only in their shape and size, but even more importantly in the number, size and shape of active zones and in the organization and size of the three pools of synaptic vesicles summarized in Table 1. Interestingly, some structural parameters such as bouton size, pre-and postsynaptic density surface area, content of mitochondria, and synaptic vesicles pools are in some cortical synapses well correlated but in others, no or only a weak correlation between several structural subelements are found (Rollenhagen 2015Dufour et al 2016;Hsu et al 2017;Bopp et al 2017;Rodriguez-Moreno et al 2018). The most striking difference at cortical synaptic boutons is the total pool, and the three functionally defined pools of synaptic vesicles, namely the RRP, the RP and resting pools.…”
Section: Synaptic Boutons In the Neocortex Of Rodents And Non-human Pmentioning
confidence: 99%
“…In contrast, only a few coherent and quantitative structural studies exist for synaptic boutons in the rodent neocortex (Rollenhagen et al 2015(Rollenhagen et al , 2018Dufour et al 2016;Bopp et al 2017;Hsu et al 2017;Rodriguez-Moreno et al 2018) and non-human primate neocortex Martin 2006, 2009;Freese and Amaral 2006;Hsu et al 2017). These studies have demonstrated, for example, layer, region and gender specific differences in the density of synaptic boutons (Alonso-Nanclares et al 2008).…”
Section: Synaptic Boutons In the Neocortex Of Rodents And Non-human Pmentioning
confidence: 99%